Mesenteric paraganglioma a rare mesenteric tumor - Nichkaode, Prabhat Bhaskarrao; Patel, Sachin Kumar (International Surgery Journal, 2017)
Paragangliomas arise from chromaffin tissue, most commonly found in the Zuckerkandl body, the sympathetic plexus of the urinary bladder, the kidneys, the heart or in the sympathetic ganglia of the head or neck. Some paragangliomas have been described in the Gastrointestinal System, the majority of which were associated with the duodenum. Only a very select few were described to arise from the mesentery.